Students' School Achievement and Parents' Level of Education in the Context of Family Environment - Radovan M. Antonijević; Dragana B. Radenović (University of Belgrade, Teacher Education Faculty, 2024)
The goal of the research is to determine the basic characteristics of the connection between students' school achievement in mathematics and the Serbian Language and their parents' education and family structure. A total of 600 seventh-grade students participated in the research. A descriptive method was used, and the data was collected using a survey technique. Based on the analysis of the results, it can be concluded that the level of education of both mother and father is equally important for students' achievement at school. Life in a complete family impacts student achievement in mathematics and the Serbian language. The mentioned factors have the same importance of influence, in the same order, both in teaching mathematics and in teaching the Serbian language. However, it is evident that the structure of the family, as a predictor of achievement, has a very small influence in terms of percentage relative to the educational level of the parents.